Robots as social companions for space exploration - Matthieu J. Guitton (Computers in Human Behavior: Artificial Humans)
Space is the next border that humanity needs to cross to reach new developments. Yet, space exploration faces numerous challenges, especially when it comes to hazard putting in danger human health. While a lot of efforts are being made to mitigate the impact of space travel on physical health, mental health of space travelers is also highly at risk, notably due to isolation and the associated lack of meaningful social interactions. Given the social potentiality of artificial agents, we propose here that social robots could play the role of social partners to mitigate the impact of space travel on mental health. We will explore the logics behind using robots as partners for in-space social training. We will then identify what are the advantages of using social robots for this purpose, either for crew members and passengers on shorter spaceflights, or for potential colons for possible future longer-term space exploration missions.